Transcriptomic analysis reveals sex-specific patterns in the hippocampus in Alzheimer’s disease - Onisiforou, Anna; Christodoulou, Christiana C.; Zamba-Papanicolaou, Eleni; Zanos, Panos; Georgiou, Polymnia (Frontiers in Endocrinology, 2024)
Background: The hippocampus, crucial for memory and learning, is one of the earliest brain regions affected in Alzheimer's Disease (AD) and undergoes adult neurogenesis. Women face double the risk of AD compared to men, highlighting the need to understand sex differences in hippocampal function for AD susceptibility. Methods: We conducted a thorough analysis of bulk mRNA postmortem samples from the whole hippocampus (GSE48350, GSE5281) and its CA1 and CA3 subfields (GSE29378). Our goal was to perform a comparative molecular signatures analysis, exploring sex-specific differences in AD. This involved comparing gene expression profiles among male controls (M-controls) vs. female controls (F-controls), females with AD (F-AD) vs. F-controls, males with AD (M-AD) vs. M-controls, and M-AD vs. F-AD. Additionally, we identified AD susceptibility genes interacting with menopause hormone replacement drug targets, particularly the ESR1 and ESR2 genes, along with GPER1. Results: The hippocampal analysis revealed contrasting patterns between M-AD vs. M-controls and F-AD vs. F-controls, as well as M-controls vs. F-controls. Notably, BACE1, a key enzyme linked to amyloid-beta production in AD pathology, was found to be upregulated in M-controls compared to F-controls in both CA1 and CA3 hippocampal subfields. In M-AD vs. M-controls, the GABAergic synapse was downregulated, and the Estrogen signaling pathway was upregulated in both subfields, unlike in F-AD vs. F-controls. Analysis of the whole hippocampus also revealed upregulation of the GABAergic synapse in F-AD vs. F-controls. While direct comparison of M-AD vs. F-AD, revealed a small upregulation of the ESR1 gene in the CA1 subfield of males. Conversely, F-AD vs. F-controls exhibited downregulation of the Dopaminergic synapse in both subfields, while the Calcium signaling pathway showed mixed regulation, being upregulated in CA1 but downregulated in CA3, unlike in M-AD vs. M-controls. The upregulated Estrogen signaling pathway in M-AD, suggests a compensatory response to neurodegenerative specifically in males with AD. Our results also identified potential susceptibility genes interacting with ESR1 and ESR2, including MAPK1, IGF1, AKT1, TP53 and CD44. Conclusion: These findings emphasize sex-specific disease mechanisms in AD pathogenesis. Region-specific analysis provides detailed insights into localized changes in the hippocampus, capturing sex-specific molecular patterns in AD susceptibility and progression.